Analytical and CAD Modeling of Double-Acting Reciprocating Compressor Components - Pramod K Jadhao; Dr Sachin R Karale; Nitin N Pawar; Brijkishor Sah (Utilitas Mathematica, 2025)
The design and performance analysis of a double-acting reciprocating air compressor, created to satisfy industrial needs for high-volume compressed air output in a short amount of running time, are presented in this study. In order to maintain a working pressure of 9 kg/cm2, the study entails the methodical engineering of crucial parts, such as the piston bore diameter, stroke length ratio, flange assembly, bolts, studs, and piston rings. A commercially available single-acting reciprocating compressor (Model SS 05090 HN, ELGI manufacture) with a piston displacement of 21.4 CFM and an operating speed of 925 rpm is the basis for the design framework. Switching to a double-acting mechanism greatly increases the compressor output and efficiency. The components were modeled, stress analyses were performed, and geometric assessments were carried out using Computer-Aided Design (CAD) tools. According to the investigation, the double-acting arrangement enhances operational effectiveness, cost-effectiveness, and economic viability and achieves outstanding performance. The results confirm that double-acting compressors are a more efficient option in industrial settings than traditional single-acting systems.